Green University as an Element of Forming a Sustainable Public Health System - Kostyantyn Kyrychenko; Dmytro Laznenko; Yaroslav Reshetniak (Health Economics and Management Review)
Universities have always had a significant impact on the development of society as centers of scientific and social progress. As a result, their role in the implementation of all sustainable development goals set by the UN is constantly growing. This is primarily due to the expansion of their ecosystem and significant progress towards the greening of the university environment through the introduction of the concept of 'green campus'. However, there is a logical need to analyze the effectiveness of such an approach through the prism of satisfaction of all participants in the educational and scientific process, especially in the context of ensuring a healthy environment as an element of public health. That is why the authors of this article try to determine the degree of correlation between the implementation of the concept of 'green university' and the formation of a healthy environment in higher education institutions as components of sustainable public health. In their work they are guided by classical methods of scientific research such as systems analysis, scientific abstraction, synthesis, statistical analysis. They also use VOSviewer software to analyze more than 1,000 publications in the Scopus database and address green campus and healthy environments. During the study of bibliographic data, considerable attention was paid to the identification of clusters of key concepts used by scientists in the study of these issues. As one of the results of the research, the authors present an analysis of the spatial-cluster relationship of scientists, which reveals the main clusters and significant interest of scientists from China and the United States in implementing and improving the concepts of 'green university'. However, the results of this analysis are insufficient, because: there was a lack of holistic understanding of scientists from different countries of the essence and objectives of the concept of 'green university'; low level of study of correlations between the attempt to form environmentally friendly higher education institutions and the formation of a healthy environment in them.